Carotenoid composition of a New Zealand (Evechinus chloroticus) and an Australian (Heliocidaris erythrogramma) sea urchin in relation to gonad colour. (30th May 2018) - Brewster, Jodi; Garama, Daniel; Lamare, Miles; Carne, Alan
Abstract: Sea urchins are commercially harvested for their edible gonads, also known as roe or uni. Most species, particularly those from the Northern hemisphere are reported to exhibit limited variation in gonad colour, which is proposed to be due to carotenoid pigments. The commercially harvested species from New Zealand, Evechinus chloroticus, and from Australia, Heliocidaris erythrogramma, however, exhibit considerable gonad colour variation, ranging from a culinary desirable light yellow/orange to an undesirable brown. Gonads from E. chloroticus and H. erythrogramma were characterized spectrophotometrically and the carotenoid content extracted and analysed by reversed‐phase high‐performance liquid chromatography. The main carotenoid found in the gonads of both species was 9′‐ cis ‐echinenone, with lower levels of all‐ trans ‐echinenone, lutein and isozeaxanthin. Carotenoid composition contributed to the yellow/orange colour components of the gonads, but was not correlated with the darker roe coloration observed in some E. chloroticus individuals. Our results highlight important considerations relating sea urchin gonad coloration to carotenoid content and as such will provide useful information for the future aquaculture and processing of these two species.